AN ANALYSIS OF PRESCRIPTION PATTERN, ADHERENCE TO PHARMACOTHERAPY AND QUALITY OF LIFE IN PEMPHIGUS VULGARIS PATIENTS - HIRAPARA, RIDHDHI K.; SINGH, ANIL P.; KARELIA, BHARTI N.; SINHA, ANITA (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: Pemphigus Vulgaris [PV] is a chronic autoimmune disease. Corticosteroids and Immunosuppressants are the main line of treatment. The aim of this study was to evaluate the prescription pattern and patient adherence behavior with therapy. We determined the association between patient adherence and quality of life in patients with pemphigus vulgaris. Methods: A prospective observational study was conducted from February 2020 to May 2021. The age and sex of patients who were diagnosed with PV within 1 mo period and confirmative histopathological findings in Biopsy were included in the study. A total of 35 patients were analyzed and patients were reviewed for medication adherence and quality of life by using MMAS-8 and WHOQOL respectively, monthly till 3 mo after initiation of therapy. Statistical analysis was done by using Epi Info version 7.1.5. Results: Out of 140 prescriptions, vitamin C and zinc were the most common drug prescribed in 129 prescriptions followed by prednisolone prescribed in 128 prescriptions. The average number of drugs per encounter was 8.67. 97.56 % of drugs were prescribed by generic names. No significant improvement was seen in the adherence behavior of patients from 1st follow-up to 3rd follow-up. It was observed that physical, psychological, and environmental domains have significant associations with medication adherence in all 3 follow-up visits. Conclusion: It was concluded that Polypharmacy and inappropriate use of medicines may decrease the adherence behavior of patients to the therapy. Low adherence to pharmacotherapy affects the quality of life in PV patients. This study is beneficial for raising awareness about treatment adherence and also encouraging the development of appropriate interventions.